The "Aku Bisa" Program; Efforts to Train Early Childhood Independence - Fathor Rozi; Faizatul Widat; Latifatus Saleha; Arofatus Zainiyah; Siti Nur Aisyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood is a period that requires guidance and development of self-development in order to train independence. However, training independence in early childhood cannot be done carelessly and must start from small things. This study aims to examine efforts to train early childhood independence through the "I Can" program based on self-accustoming at Sinar Harapan Kindergarten, Kedopok, Probolinggo. This research uses a descriptive qualitative approach with a case study type to examine the program. After the data were collected through interviews and observations, the data analysis techniques were data reduction, data display, and data verification. The results showed that the "Aku Bisa" program consisted of routine activities carried out from the time students arrived at school until the time of learning was over and evaluation with the parents of students every two months. The implication is that efforts to train children's independence will be successful if parents also support program activities and monitor their development